Plazomicin: A Next‐Generation Aminoglycoside. Issue 1 (8th January 2019) - Shaeer, Kristy M.; Zmarlicka, Monika T.; Chahine, Elias B.; Piccicacco, Nicholas; Cho, Jonathan C.
Abstract : Plazomicin is a novel aminoglycoside antibiotic that binds to the bacterial 30S ribosomal subunit, thus inhibiting protein synthesis in a concentration‐dependent manner. Plazomicin displays a broad spectrum of activity against aerobic gram‐negative bacteria including extended‐spectrum β‐lactamase–producing Enterobacteriaceae, carbapenem‐resistant Enterobacteriaceae, and organisms with aminoglycoside‐modifying enzymes. In a large phase III clinical trial, plazomicin was shown to be noninferior to meropenem in the treatment of complicated urinary tract infections (cUTIs) with respect to the coprimary efficacy end points of the microbiologically modified intent‐to‐treat composite cure rate at day 5 (plazomicin 88% [168/191 subjects] vs meropenem 91.4% [180/197]) and at the test‐of‐cure visit (plazomicin 81.7% [156/191] vs meropenem 70.1% [138/197]). In a small phase III clinical trial, plazomicin was shown to be effective in the treatment of infections caused by carbapenem‐resistant Enterobacteriaceae. It was associated with a lower all‐cause mortality or significant disease‐related complication rate (23.5% [4/17]) compared with colistin (50% [10/20]). The most common adverse reactions associated with plazomicin are decreased renal function, diarrhea, hypertension, headache, nausea, vomiting, and hypotension. As with other aminoglycosides, plazomicin may cause neuromuscular blockade, ototoxicity, and fetal harm in pregnant women. Due to limited efficacy and safety data, plazomicin is indicated for the treatment of cUTIs in adults with limited or no alternative treatment options, using a dosage regimen of 15 mg/kg intravenously every 24 hours for 4–7 days. Dosage reductions and therapeutic drug monitoring are warranted in patients with moderate or severe renal impairment. Plazomicin is not recommended in patients with severe renal impairment including those receiving renal replacement therapy. With the approval of plazomicin, clinicians now have an additional option for the treatment of adults with cUTIs, particularly those caused by multidrug‐resistant gram‐negative rods.